Mitochondrial Quality Control Orchestrates the Symphony of B Cells and Plays Critical Roles in B Cell-Related Diseases - Wuhao Li; Peiyang Cai; Ye Xu; Weihong Tian; Licong Jing; Qiaoyi Lv; Yangjing Zhao; Hui Wang; Qixiang Shao (Journal of Immunology Research)
B cells are essential for humoral immune response due to their ability to secrete antibodies. The development of B cells from the bone marrow to the periphery is tightly regulated by a complex set of immune signals, and each subset of B cells has a unique metabolic profile. Mitochondria, which serve as cellular energy powerhouses, play an essential role in regulating cell survival and immune responses. To maintain metabolic homeostasis, mitochondria dynamically adjust their morphology, distribution, and mass via biogenesis, fusion and fission, translocation, and mitophagy. Despite its extreme importance, the role of mitochondrial quality control (MQC) in B cells has not been thoroughly summarized, unlike in T cells. This article aims to review the mechanism of MQC that shapes B cell fate and functions. In addition, we will discuss the physiological and pathological implications of MQC in B cells, providing new insights into potential therapeutic targets for diseases associated with B cell abnormalities.